Cardiac Herniation with Torsion of Right Pulmonary Artery: Status Post Urgent Left Pneumonectomy - L, Pietropaoli; S, Renaud; A, Doucet; L, Ferri; J, Spicer; F, Donatelli; F, Marinangeli (Cardiology and Cardiovascular Medicine, 2019)
Cardiac herniation is a rare complication of intrapericardial lung resection, typically occurring within the first twenty-four hours. Considering that this condition carries a high mortality rate despite prompt management, early diagnosis is key. Since clinical manifestations can be variable, the use of imaging modalities coupled with a high index of suspicion is critical to making the correct diagnosis. In this article, a case of acute cardiac herniation post left pneumonectomy diagnosed with the help of an intraoperative transesophageal echocardiography (TEE) is presented.